Analysis of carbon stock and radial growth of trees through tree ring analysis in pine forest of linga guthi in Bhaktapur, Nepal - Chhukan, Saphalta; Karmacharya, Siddi Bir; Maharjan, Sanu Raja (Journal of Natural History Museum, 2018)
Forests are the integral to the global carbon cycle. These ecosystems sequester carbon in the plant biomass and in the soil. The study was carried out in Linga Guthi Community Forest of Bhaktapur to estimate carbon Stock and radial growth of Pinus roxburghii through tree ring analysis. A total of 32 circular plots of 250 m2 area were laid down randomly. Subplots were made for study of saplings, Litter, herbs and soil. For tree ring analysis, tree core samples were collected from different blocks of forest. Ring widths were measured using TSAP-Win Software attached to a LINTAB measuring system. For tree ring analysis, COFECHA and ARSTAN program were used. The average carbon stock of Linga Guthi Community Forest was 272.22±17.36 t/ha. Similarly, it has storage of 206.87± 4.47 t/ha AGTC, 41.37±2.19 t/ha BGTC, 23.814±1.00 t/ha SOC. The carbon sequestration rate of the forest was 2.22 Ct/ha/year. The average radial growth of pine trees in the forest was found to be 2.06 ± 0.13 mm/year. The maximum radial growth was 4.47 mm/yr. The oldest tree recorded in this forest was158 years with 58 cm diameter. However the average age of the forest was 98 years. The ring width chronology of 158 years was prepared for pine tree extending from 1854 to 2013 A.D.